2019
DOI: 10.3390/app9142897
|View full text |Cite
|
Sign up to set email alerts
|

Cockle Shell-Derived Calcium Carbonate (Aragonite) Nanoparticles: A Dynamite to Nanomedicine

Abstract: Cockle shell is an external covering of small, salt water edible clams (Anadara granosa) that dwells in coastal area. This abundant biomaterial is hard, cheap and readily available with high content of calcium carbonate in aragonite polymorphic form. At present, cockle shell-derived calcium carbonate nanoparticles (CSCaCO3NPs) with dual applications has remarkably drawn significant attention of researchers in nanotechnology as a nanocarrier for delivery of different categories of drugs and as bone scaffold due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 138 publications
0
17
0
Order By: Relevance
“…Other osteochondral scaffold designs have incorporated specific ceramic formulations such as aragonite and wollastonite as minerals for the bone layer. Aragonite is a calcium carbonate material derived from cockle shell [ 109 ], while wollastonite is a calcium silicate mineral [ 110 ], both of which are bioactive and help promote subchondral bone repair. An aragonite scaffold combined with hyaluronate as the cartilage phase completely regenerated an osteochondral defect in 6 of 7 animals at 12 months after implantation in a goat model, exhibiting formation of hyaline cartilage and subchondral bone with strong integration into adjacent native tissues [ 74 ].…”
Section: Multiphasic Scaffold Biomaterialsmentioning
confidence: 99%
“…Other osteochondral scaffold designs have incorporated specific ceramic formulations such as aragonite and wollastonite as minerals for the bone layer. Aragonite is a calcium carbonate material derived from cockle shell [ 109 ], while wollastonite is a calcium silicate mineral [ 110 ], both of which are bioactive and help promote subchondral bone repair. An aragonite scaffold combined with hyaluronate as the cartilage phase completely regenerated an osteochondral defect in 6 of 7 animals at 12 months after implantation in a goat model, exhibiting formation of hyaline cartilage and subchondral bone with strong integration into adjacent native tissues [ 74 ].…”
Section: Multiphasic Scaffold Biomaterialsmentioning
confidence: 99%
“…Remarkable strength, unique electrical properties, functionalization-enhanced solubility, penetration to cell cytoplasm and to the nucleus, as a carrier for gene delivery [ 27 , 28 ]…”
Section: Figurementioning
confidence: 99%
“…These shells are discarded in large amounts in the food industry. Cockle shells have a high calcium carbonate content [ 9 ]. These shells are abundantly available at a minimal cost, and in vitro studies have demonstrated that the calcium carbonate derived from cockle shells is biocompatible [ 10 ].…”
Section: Introductionmentioning
confidence: 99%